2002
DOI: 10.1074/jbc.m205034200
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Transport in Saccharomyces cerevisiae

Abstract: The fatty acid transport protein Fat1p functions as a component of the long-chain fatty acid transport apparatus in the yeast Saccharomyces cerevisiae. Fat1p has significant homologies to the mammalian fatty acid transport proteins (FATP) and the very long-chain acylCoA synthetases (VLACS). In order to further understand the functional roles intrinsic to Fat1p (fatty acid transport and VLACS activities), a series of 16 alleles carrying site-directed mutations within FAT1 were constructed and analyzed. Sites ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 50 publications
3
64
0
Order By: Relevance
“…For example, it is generally assumed that 10,16-dihydroxypalmitate and other cutin precursors are transferred through the plasma membrane (or an endomembrane) to the cell exterior. In many cases, cross-membrane transport of fatty acids requires an acyl-CoA synthetase activity on the distal side of the membrane (Schaffer and Lodish, 1994;Gargiulo et al, 1999;Zou et al, 2002), and acyl-CoAs have been shown to be substrates for cutin synthesis in vitro (Croteau and Kolattukudy, 1974). Thus, LACS2 may act either at the external face of the plasma membrane or the lumenal face of the ER or Golgi to synthesize hydroxyacyl-CoA substrates for cutin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is generally assumed that 10,16-dihydroxypalmitate and other cutin precursors are transferred through the plasma membrane (or an endomembrane) to the cell exterior. In many cases, cross-membrane transport of fatty acids requires an acyl-CoA synthetase activity on the distal side of the membrane (Schaffer and Lodish, 1994;Gargiulo et al, 1999;Zou et al, 2002), and acyl-CoAs have been shown to be substrates for cutin synthesis in vitro (Croteau and Kolattukudy, 1974). Thus, LACS2 may act either at the external face of the plasma membrane or the lumenal face of the ER or Golgi to synthesize hydroxyacyl-CoA substrates for cutin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Using site-directed mutagenesis of the FATP1 orthologue in yeast Fat1p, fatty acid uptake and fatty acid activation are generally but not universally coupled processes (29). Four FAT1 alleles distinguish fatty acid transport and very long chain acyl-CoA synthetase activity, suggesting separable functions.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it is highly speculative that the first 185 amino acids encoded by exons 1 and 2 would present a peptide with biological activity, it is worthwhile noting that this region is homologous to fragments of FATP1 that would include the entire extracellular N terminus, the transmembrane region, and cytoplasmic membraneassociated sequences (38). Because FATPs may be multifunctional proteins with separable residues involved in LCFA transport and activation (39), the hypothetical fusion proteins could retain some aspects of FATP4 function, such as LCFA transport, or interaction with other proteins, for instance longchain acyl-CoA synthetases (40) or other FATPs (19). Although the causes of neonatal mortality, described by Moulson et al (30) and Herrmann et al (22), may differ from the embryonic death described in this article, both lethalities ultimately underscore the importance of FATP4-mediated LCFA uptake/ activation for normal physiology.…”
Section: Table IIImentioning
confidence: 99%